2022
DOI: 10.1038/s43587-021-00165-w
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-2 preserves integrity of the articular cartilage to protect against osteoarthritis

Abstract: Osteoarthritis (OA) is an aging-related degenerative joint disease, which has no cure partly due to limited understanding of its pathological mechanism(s). Here we report that the focal adhesion protein Kindlin-2, but not Kindlin-1 or -3, is highly expressed in articular chondrocytes of the hyaline cartilage, which is dramatically decreased in the degenerated articular cartilage of aged mice and patients with OA. Inducible deletion of Kindlin-2 in chondrocytes at adult stage leads to spontaneous OA and much se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 64 publications
(54 reference statements)
2
27
0
Order By: Relevance
“…Our previous studies have shown that both Kindlin-2 and Pinch proteins are required for chondrogenesis and skeletal development in mice ( Wu et al, 2015 ; Lei et al, 2020 ). Most recently, we have demonstrated that the expression of Kindlin-2 is also critical for the maintenance of cartilage homeostasis during adulthood ( Wu et al, 2022a ; Lai et al, 2022 ). It is interesting to compare the phenotypes of mice lacking Kindlin-2 in adult cartilage (Aggrecan CreERT2 ; Kindlin-2 flox/flox ) in our previous study with mice lacking Pinch1/2 in adult cartilage (Aggrecan CreERT2 ; Pinch1 flox/flox ; Pinch2 −/− ) in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies have shown that both Kindlin-2 and Pinch proteins are required for chondrogenesis and skeletal development in mice ( Wu et al, 2015 ; Lei et al, 2020 ). Most recently, we have demonstrated that the expression of Kindlin-2 is also critical for the maintenance of cartilage homeostasis during adulthood ( Wu et al, 2022a ; Lai et al, 2022 ). It is interesting to compare the phenotypes of mice lacking Kindlin-2 in adult cartilage (Aggrecan CreERT2 ; Kindlin-2 flox/flox ) in our previous study with mice lacking Pinch1/2 in adult cartilage (Aggrecan CreERT2 ; Pinch1 flox/flox ; Pinch2 −/− ) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the Pinch2 gene is globally inactivated in the Aggrecan CreERT2 ; Pinch1 flox/flox ; Pinch2 −/− mice. For inducible deletion of the Pinch1 gene in aggrecan-expressing chondrocytes, 2-month-old male Aggrecan CreERT2 ; Pinch1 flox/flox ; Pinch2 −/− mice were administrated with tamoxifen (Sigma T5648, 100 mg/kg per body weight/day) via intraperitoneal injections as previously described ( Wu et al, 2022a ; Wu et al, 2022b ; Chen et al, 2022 ). Age-matched male Aggrecan CreERT2 ; Pinch1 flox/flox ; Pinch2 −/− mice were administrated with corn oil and used as the control group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations